2016
DOI: 10.1016/j.plantsci.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and abscisic acid supplementation influences somatic embryo maturation and hormone endogenous levels during somatic embryogenesis in Podocarpus lambertii Klotzsch ex Endl.

Abstract: Here we propose a protocol for embryogenic cultures induction, proliferation and maturation for the Brazilian conifer Podocarpus lambertii, and investigated the effect of abscisic acid (ABA) and glutathione (GSH) supplementation on the maturation phase. ABA, zeatin (Z) and salicylic acid (SA) endogenous levels were quantified. Number of somatic embryos obtained in ABA-supplemented treatment was significant higher than in ABA-free treatment, showing the relevance of ABA supplementation during somatic embryos ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…This is supported by the results of Quiroz-Figueroa et al 46 , who suggested that a low SA concentration can induce the reprogramming of somatic cells, forcing them into the embryogenic stage, while at a high concentration this reprogramming may be inhibited. This confirmed the correlation between a lower endogenous SA concentration and improved callus induction 47 . Although most previous studies only focused on the hormone levels in the calli produced by tissue culturing, it is evident that greater levels of endogenous JA, IAA and GA hormones in explants are important for garlic callus formation and proliferation.…”
Section: Discussionsupporting
confidence: 80%
“…This is supported by the results of Quiroz-Figueroa et al 46 , who suggested that a low SA concentration can induce the reprogramming of somatic cells, forcing them into the embryogenic stage, while at a high concentration this reprogramming may be inhibited. This confirmed the correlation between a lower endogenous SA concentration and improved callus induction 47 . Although most previous studies only focused on the hormone levels in the calli produced by tissue culturing, it is evident that greater levels of endogenous JA, IAA and GA hormones in explants are important for garlic callus formation and proliferation.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, in peach seeds, phosphates and ribosides of the DHZ and iP-type are the predominant CKs and functions like embryo formation and growth, division of endosperm primary nucleus, endosperm cellularization and endosperm cell division have been attributed to them (Arnau et al, 1999). So, opposite to Pacheco de Freitas et al (2016) active CK levels seem to be important during the later stages of embryo development and maturation showing large amounts of these phytohormones in treatments with high production of mature embryos.…”
Section: Discussionmentioning
confidence: 86%
“…Factors, which induced somatic embryogenesis, may directly or indirectly affect the auxin balance and/ or responses within the cells (Fehér 2015 and literature therein). According to Fraga et al (2016) cytokinins are also important during the initial phase of somatic embryogenesis, but not for the later stages of embryo development and maturation. The various cell-types exhibit specific responses to the same stress factor, what can explain the striking influence of the genotype, explant source, culture, and stress condition on the embryogenic capability.…”
Section: Discussionmentioning
confidence: 99%